A multi-objective optimization-based layer-by-layer blade-coating approach for organic solar cells: rational control of vertical stratification for high performance - Sun, Rui; Guo, Jie; Wu, Qiang; Zhang, Zhuohan; Yang, Wenyan; Guo, Jing; Shi, Mumin; Zhang, Yaohong; Kahmann, Simon; Ye, Long; Jiao, Xuechen; Loi, Maria A.; et al. (Energy and Environmental Science, 2019)
A major breakthrough in organic solar cells (OSCs) in the last thirty years was the development of the bulk heterojunction (BHJ) solution processing strategy, which effectively provided a nanoscale phase-separated morphology, aiding in the separation of Coulombically bound excitons and facilitating charge transport and extraction. Compared with the application of the layer-by-layer (LbL) approach proposed in the same period, the BHJ spin-coating technology shows overwhelming advantages for evaluating the performance of photovoltaic materials and achieving more-efficient photoelectric conversion. Thus, in this study, we have further compared the BHJ and LbL processing strategies via the doctor-blade coating technology because it is a roll-to-roll compatible high-throughput thin film fabrication route. We systematically evaluated multiple target parameters, including morphological characteristics, optical simulation, physical kinetics, device efficiency, and blend stability issues. It is worth emphasizing that our findings disprove the old stereotypes such as the BHJ processing method is superior to the LbL technology for the preparation of high-performance OSCs and the LbL approach requires an orthogonal solvent and donor/acceptor materials with special solubility. Our studies demonstrate that the LbL blade-coating approach is a promising strategy to effectively reduce the efficiency-stability gap of OSCs and even a superior alternative to the BHJ method in commercial applications.
CRIS-Team WoS Importer:2019-10-25